HUBUNGAN POLA ASUH ORANG TUA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI SMA MUHAMMADIYAH BANGKINANG, KABUPATEN KAMPAR - Arif Rahman; Makhdalena Makhdalena; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study is to find out the relationship of parenting to student learning achievement in class XI subjects of Muhammadiyah Bangkinang High School The population of this study is all students of class XI of Muhammadiyah Bangkinang High School with a total of 20 people. The sample in this study using the census method was taken as a whole for class XI students in 2019/2020 which amounted to 20 people Data analysis techniques used using editing and scoring techniques, namely checking the completeness and filling of questionnaires or questionnaires that have been collected and providing scores on each questionnaire answer as follows: in this time there are five answer categories, namely: strongly agree, agree, hesitate, disagree, and strongly disagree. The items are scored based on the selected answers and the types of positive and negative questions. For positive questions the score moves from the answer the score is 3, 2, 1. for negative questions the suspension moves the opposite. The correlation between parenting (variable X) and economic learning achievement (variable Y) goes in the same direction. In other words, there is a positive correlation between the two.Key Words: Parenting and Learning achievements